OPPORTUNITIES FOR DEVELOPING THE INVESTMENT ENVIRONMENT IN FOOD INDUSTRY ENTERPRISES - Ravshanovich, Xamraev Nodirbek (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This scientific article focuses on the problems of attracting foreign investments in the development of the activities of food industry enterprises, developing the investment environment in the industry, and creating a transparent competitive environment in the industry. In addition, suggestions and recommendations were given on encouraging foreign investments in the activities of food industry enterprises, modernizing food industry enterprises in accordance with the requirements of the times, technical and technological updating, and developing economic mechanisms for the development of their activities